Islamic Bank Strategy in Facing Competition in The Era of Digitalization - Didih Muhamad Sudi (Nomico, 2025)
Digital transformation has brought significant changes to the global banking industry, including for Islamic banks in Indonesia. This study aims to examine the strategies implemented by Islamic banks in responding to the increasingly intense competition in the digitalization era. The method used is qualitative research with a case study approach, involving in-depth interviews with managers and practitioners of Islamic banking. The findings indicate that Islamic banks adopt several key strategies, such as the digitalization of banking services, integration of Sharia principles into digital platforms, strengthening of technological infrastructure, and enhancement of human resource capacity. In addition, collaboration with fintech companies, customer education, and the development of products tailored to the needs of the younger generation are vital components of digital adaptation efforts. Despite facing infrastructure limitations and regulatory challenges, Islamic banks demonstrate potential for growth and competitiveness through innovative strategic approaches grounded in Sharia values. This study contributes to the development of relevant business strategies for Islamic banks in the digital transformation era and may serve as a reference for policymakers and stakeholders in the Islamic finance industry.